MULTIPARENTALITY AND INHERITANCE LAW: CHALLENGES AND PERSPECTIVES IN THE COEXISTENCE OF BIOLOGICAL AND AFFECTIVE TIES - Maria Bernardo Dos Santos, Angela; Maria da Silva Mhirdaui, Rogéria; Roberto Costa, Marcos (Revista Gênero e Interdisciplinaridade, 2025)
The present research aims to investigate the institute of succession in the context of multiparental families, with special attention to the succession of ascendants. The need to scrutinize the issue is motivated by the growing plurality of family configurations in contemporary society and by the legal recognition of multiparenthood, a phenomenon that challenges the traditional interpretative structures of succession laws. In general terms, the objective aims to understand how the legislation affects the multiplicity of situations in which ascendants have a dual paternity or maternity, biological and socio-affective simultaneously. The explanation of these conditions aims to identify legal gaps and challenges and to propose a discussion on the adequacy of the legal system to the contemporary dynamics of family relations. The methodology approaches the inductive method through descriptive and qualitative research. The study covers the collection of jurisprudence, analysis of doctrinal works and review of academic articles; The data come from the reading and selection from the identified sources, and the investigation also includes discussions in specialized forums in order to map dominant currents of doctrinal argumentation. In terms of the result identified, the phenomenon of multiparenthood raises many doubts in the succession issue. There are different doctrinal currents: considering that the two paternities, biological and socio-affective, need equal value as proof of the bond between parent and child. However, there are still those who believe in objective criteria as a way to avoid patrimonial conflicts. In short, the legal system must be modernized to keep up with changes in family configurations. Explaining multiparenthood in succession law can offer a safeguard for all involved. The evolution of legislation is crucial to ensure that justice reflects reality.